E-Government in Indonesia: Mapping Innovation, Overcoming Challenges, and Learning from Other Countries' Experiences - Yanto, Febri; Sugito; Savitri, Evi; Nurdin, Ismail (Manunggal Halim Jaya, 2025)
The implementation of e-government in Indonesia has become a key pillar in the digital transformation of government, aiming to improve the quality of public services. Despite significant progress in the adoption of digital technology, Indonesia is still faced with various challenges, such as infrastructure gaps between urban and rural areas, limited human resource competencies, and bureaucratic obstacles that slow down adaptation to new technologies. This research maps innovations in e-government in Indonesia and compares them with best practices in developed countries, such as South Korea and Singapore, which have successfully implemented digital systems inclusively and effectively. Based on a mixed qualitative and quantitative approach, this research evaluates the impact of digital innovations on efficiency and public participation in public services. The results show the importance of cross-sector collaboration, capacity building of state apparatus, and simplification of regulations to accelerate the adoption of inclusive e-government. By using advanced technologies such as artificial intelligence and blockchain, Indonesia can strengthen a responsive and sustainable e-government system. This research provides strategic policy recommendations to support the improvement of efficient and equitable public services across Indonesia.